#### Answer

x=-17.5

#### Work Step by Step

Simplifying
14x + 14(3 + -2x) + 7 = 4 + -1x + 5(2 + -3x)
14x + (3 * 14 + -2x * 14) + 7 = 4 + -1x + 5(2 + -3x)
14x + (42 + -28x) + 7 = 4 + -1x + 5(2 + -3x)
Reorder the terms:
42 + 7 + 14x + -28x = 4 + -1x + 5(2 + -3x)
Combine like terms: 42 + 7 = 49
49 + 14x + -28x = 4 + -1x + 5(2 + -3x)
Combine like terms: 14x + -28x = -14x
49 + -14x = 4 + -1x + 5(2 + -3x)
49 + -14x = 4 + -1x + (2 * 5 + -3x * 5)
49 + -14x = 4 + -1x + (10 + -15x)
Reorder the terms:
49 + -14x = 4 + 10 + -1x + -15x
Combine like terms: 4 + 10 = 14
49 + -14x = 14 + -1x + -15x
Combine like terms: -1x + -15x = -16x
49 + -14x = 14 + -16x
Solving
49 + -14x = 14 + -16x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '16x' to each side of the equation.
49 + -14x + 16x = 14 + -16x + 16x
Combine like terms: -14x + 16x = 2x
49 + 2x = 14 + -16x + 16x
Combine like terms: -16x + 16x = 0
49 + 2x = 14 + 0
49 + 2x = 14
Add '-49' to each side of the equation.
49 + -49 + 2x = 14 + -49
Combine like terms: 49 + -49 = 0
0 + 2x = 14 + -49
2x = 14 + -49
Combine like terms: 14 + -49 = -35
2x = -35
Divide each side by '2'.
x = -17.5
Simplifying
x = -17.5